(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
We have synthesized new derivatives of 1-amino-2-oxoalkylisoindole. 2-(2-Hydroxyethyl)-isoindolium bromide and 2-(3-methoxypropyl)-isoindolium bromide were synthesized with the ordinary reaction of (2-bromomethyl)-benzonitrile with correspondent oxoalkylamines with the following cyclization. (2-Methoxymethyl)-isoindolium chloride was obtained with the Delepine reaction from the salt formed with (2-bromomethyl)-benzonitrile and urotropine. With the help of obtained compounds, we have investigated the reactivity of 1-amino-2-alkylisoindoles in the cycloaddition reactions with N-phenylmaleimide. The main tautomeric form of 1-amino-2-alkylisoindoles is iminoform. However, the presence of the isoindole tautomeric form in equilibrium grants the possibility of 1-amino-2-alkylisoindoles undergoes Diels-Alder reactions extends the Curtin–Hammett principle. We have investigated that 1-amino-2-oxoalkylisoindole reacts with N-phenylmaleimide in the ration 1:2 respectively. The main product in this reaction is 4-amino-benzo[f]isoindole, which is the result of the complex rearrangement including Michael reaction and Diels-Alder [4+2]-cycloaddition. We have shown that 1-amino-2-alkylisoindoles react with maleimides like 1-amino-2-arylisoindoles instead of 1-unsubstituted aminoisoindole, which reacts with maleimides with the formation of bis-Michael adduct, or 1,2-diarylisoindole, which exists only in isoindole form, so reacts with maleimides in classic way with the formation of Diels-Alder adduct or Michael adduct depending on reaction conditions and doesn’t undergo any rearrangements. We have established that the reaction of 1-amino-2-oxoalkylisoindole affects the nature of the solvent. Thus, the reaction in methanol leads to oxidation and degradation forming a mixture of unidentified products. When used as a solvent dichloromethane adduct of the rearrangement of the second type retrieved in pure state. The structure of all compounds described with 1H NMR spectroscopy.